2014
DOI: 10.1002/ptr.5135
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Effects of Baicalein on Hepatocellular Carcinoma Cells

Abstract: The therapeutic potential of baicalein against hepatoma cells was evaluated in vitro and in vivo. In cell viability assays, baicalein showed significant cytotoxicity against the hepatocellular carcinoma cell lines H22, Bel-7404, and Hep G2 and moderate cytotoxicity against immortalized human hepatocytes. Baicalein induced G0/G1-phase arrest in hepatocellular carcinoma cells, inhibited AKT, and promoted the degradation of β-catenin and cyclin D1 without activation of GSK-3β. Furthermore, baicalein significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 19 publications
(20 reference statements)
5
46
0
Order By: Relevance
“…Previous studies have reported that baicalein could arrest the cell cycle of HCC cells at all three phase, including G0/G1, S and G2/M. For instance, Zheng et al [4] found that baicalein could induced G0/G1 arrest in Bel-7404 cell line; Yu et al [30] reported that baicalein cause cell cycle arrest at S phase in HepG2 and SMMC-7721 cell lines; whereas the Kuo et al [31] study showed baicalein exerted cytotoxic effect on J5 cells resulting in G2/M arrest, these previous studies indicated that there are substantial differences in mechanism of the cell cycle arrest induced by baicalein for different HCC cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that baicalein could arrest the cell cycle of HCC cells at all three phase, including G0/G1, S and G2/M. For instance, Zheng et al [4] found that baicalein could induced G0/G1 arrest in Bel-7404 cell line; Yu et al [30] reported that baicalein cause cell cycle arrest at S phase in HepG2 and SMMC-7721 cell lines; whereas the Kuo et al [31] study showed baicalein exerted cytotoxic effect on J5 cells resulting in G2/M arrest, these previous studies indicated that there are substantial differences in mechanism of the cell cycle arrest induced by baicalein for different HCC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…1), a purified flavonoid compound with defined chemical structure extracted from the dry roots of Scutellaria radix that is a broadly used herb in China, has been demonstrated that it has potential anti-tumor effects on many types of cancer cells, including HCC [4]. Previous studies have demonstrated that baicalein can inhibit the growth, invasion and metastasis of HCC through inducing cell cycle arrest and apoptosis, autophagy via several cancer-related signaling or molecules including MEK/ERK, JNK, Bcl-2, mTOR, CD24, 12-LOX, NF-κB [5-11].…”
Section: Introductionmentioning
confidence: 99%
“…Balcalein is a flavonoid, originally isolated from the roots of Scutellaria baicalensis and Scutellaria lateriflora with anticancer activity (78)(79)(80). Apigenin, present in many plants, is a natural product belonging to the flavone class, structurally similar to balcalein and 4' ,5,7-trihydroxyflavanone.…”
Section: Plasminogen Activation System As Potential Therapeutic Targementioning
confidence: 99%
“…26,27 It possesses a direct cytotoxicity to a large panel of human malignant cell lines by inducing apoptotic cell death. [26][27][28][29][30][31] The anti-cancer properties of baicalein were recently shown to be mediated through the inhibition of cell growth and induction of apoptosis in HCT116 human colon cancer cells. 28 Cell viability was significantly decreased by treatment of baicalein in a concentration-dependent manner.…”
Section: Modulation Of Anti-tumor Activitymentioning
confidence: 99%
“…35 In hepatocellular carcinoma including H22, Bel-7404 and HepG2 cell lines, treatment with baicalein showed anticancer effects by regulating the transcription of cyclin D1 via a -catenin-dependent mechanism. 29 Baicalein also affects the invasion and expression of migration signaling molecules, such as matrix metalloproteinase (MMP)-2 and MMP-9 in human hepatoma cells. 36 According to recent studies, baicalein treatment showed inhibition of migration and invasion in gastric and cervical cancer cells via transforming growth factor- and extracellular signal-regulated kinase signal pathways, respectively.…”
Section: Modulation Of Anti-tumor Activitymentioning
confidence: 99%